METODOLOGIAS ATIVAS E ENSINO DE HISTÓRIA: USOS E POSSIBILIDADES NO ENSINO FUNDAMENTAL NA REDE MUNICIPAL DE EDUCAÇÃO EM SÃO LUÍS - VIEIRA , Marco Aurélio Salazar (2023)
With the theme “Active methodologies and teaching of History: uses and possibilities in fundamental education in the municipal education network in São Luís”, this work is born from the permanent need to review educational practices related to the teaching of History in the municipal public network of São Luís in their final years of elementary school and, at the same time, propose educational solutions permeated by technology that are capable of changing the way students relate to historical knowledge. In this sense, Active Methodologies are understood here as a set of strategies and paths capable of transforming the learning process into something that places the student in the central role of transmission, stimulating their effective role as constructors and manipulators of knowledge.